2021
DOI: 10.1053/j.gastro.2020.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Tacrolimus, Deleterious Role of Age and Comorbidities in Liver Transplant Recipients With Covid-19: Results From the ELITA/ELTR Multi-center European Study

Abstract: Background and aims Despite concerns that liver transplant (LT) recipients may be at increased risk of unfavorable outcomes from COVID-19 due the high prevalence of co-morbidities, immunosuppression and ageing, a detailed analysis of their effects in large studies is lacking Methods Data from adult LT recipients with laboratory confirmed SARS-CoV2 infection were collected across Europe. All consecutive patients with symptoms were included in the analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
207
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(226 citation statements)
references
References 16 publications
11
207
5
3
Order By: Relevance
“…This scarce susceptibility replicates that of the general pediatric population and denies a role of immunosuppression as an additional risk in transplanted children. Even data from the European Liver Transplant Registry demonstrate a protective effect of the tacrolimus on the development of severe disease in adults ( 102 ).…”
Section: Resultsmentioning
confidence: 99%
“…This scarce susceptibility replicates that of the general pediatric population and denies a role of immunosuppression as an additional risk in transplanted children. Even data from the European Liver Transplant Registry demonstrate a protective effect of the tacrolimus on the development of severe disease in adults ( 102 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of severe COVID-19 infection, controlling the inflammatory response by high dose steroid is currently the best option (103). A recent study among recipients of a liver transplant with COVID-19 infection showed that the use of tacrolimus was associated with a significant reduction of mortality (104). This findings underlines that limiting the excessive T cell response, in this case by tacrolimus, is a key element in harnessing the morbidity and mortality of COVID-19.…”
Section: Implications For Covid-19 Infectionmentioning
confidence: 93%
“…376 (78%) patients required hospitalization, including 147 (39%) patients requiring ICU care and 77 (20.5%) patients who died within 1 month after the diagnosis of COVID-19 (Table 3) [52]. [6,16,20,65,67,69,70] Intraoperative considerations in suspected or confirmed COVID-19 patient [6,16,19,20] Postoperative considerations in suspected or confirmed COVID-19 patient [6,19,20,69,70] Screening with COVID-19 symptom evaluation and body temperature measurement Use of regional anesthesia The multicenter study from the European LT Registry (ELTR) is the largest study reporting the outcomes of SAR-CoV-2 infection in 243 adult symptomatic LT patients from 36 centers [53]. They found that 84% of patients required hospitalization, including ICU admission in 19% of cases.…”
Section: Sars-cov-2 Infection In Liver Transplant Recipientsmentioning
confidence: 99%
“…About 20% of LT patients died due to COVID-9, with respiratory failure being the primary cause of death. On multivariate analysis, the authors found that age > 70 years, comorbidities such as diabetes mellitus, and chronic kidney disease were independent risk factors for mortality (Table 3) [53].…”
Section: Sars-cov-2 Infection In Liver Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation